The Effect of Specialist Residency program on the Performance Indicators of Emergency Department of Hospitals in Tehran: An Interrupted Time Series Study - Morteza Rabeti; Maryam Tajvar; Maryam Sadat Askari; Marita Mohammadshahi; Ebrahim Jaffari Poyan (پژوهش‌های سلامت‌محور, 2020)
The Effect of Specialist Residency Program on the Performance Indicators of Emergency Departments in Hospitals Affiliated to Tehran University of Medical Sciences: An Interrupted Time Series Study